Systems and procedure study on Socialized Tuition Financial Assistance Program - Ang, Richard; Mercado, Mary Jane.; Ramirez, Ma. Cristina; Rosca, James; Talaue, Feroisa; Tapang, Peter (Diliman, Quezon City College of Engineering, 1991)
The group was tasked with the systems and procedures study of the Socialized Tuition and Financial Assistance Program (STFAP) of the Scholarship and Financial Assistance Service (SFAS) of the University of the Philippines. To achieve this goal, the group interviewed the supervising officer in order to get an overview of the STFAP program and the present system of granting STFAP benefits. The group also interviewed the actual personnel involved in the processing of STFAP applications in order to trace the steps taken by an application. The group was not able to witness the operation of existing application process because the study took place between the application periods.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis